Atypical arthritis in a toddler: beware, save the heart - Boopathy, Sharani; Thandapani, Kanimozhi; Arunagirinathan, Arulkumaran (International Journal of Contemporary Pediatrics, 2020)
Acute rheumatic fever still poses a dreadful threat to pediatric morbidity and mortality. A 2 year old toddler presented to us with non migratory polyarticular joint pain and swelling. General physical and systemic examination was normal. Local examination revealed swelling and tenderness of multiple small and large joints. Further evaluation fulfilled Modified Jones criteria and she was diagnosed to have acute rheumatic fever. Other close differentials were simultaneously ruled out. Child was started on naproxen because of aspirin toxicity. There was significant response for therapy and complete resolution of joint involvement was noted on follow up. We report this case to emphasize the fact that rheumatic fever might have bizarre clinical presentation and may also affect infants and toddlers deviating the typical age of onset. There is a need for earliest possible initiation of adequate management and follow up to prevent permanent cardiac complications. This warrants high index of suspicion even in uncommon age group.